An inverse analysis method for multi-linear tensile stress-crack opening relationship of 3D/4D/5D steel fiber reinforced concrete. (22nd November 2021) - Gao, Danying; Ding, Chong; Pang, Yuyang; Chen, Gang
Highlights: Analytical solutions are developed by considering multi-linear σ - w relationship. Multi-linear σ - w relationship is obtained by inverse analysis method. Flexural properties of SFRC beam with 3D, 4D and 5D steel fubers are predicted. Abstract: The tensile stress-crack opening ( σ - w ) relationship of steel fiber reinforced concrete (SFRC) is of much importance for calculating the resistance of structures at serviceability and ultimate limit state. In this paper, the analytical solutions for the flexural response of SFRC beams were firstly developed by considering the multi-linear σ - w relationship of SFRC. Then, the parameters of the multi-linear σ - w relationship were obtained by using an inverse analysis method based on the analytical solutions and the experimental results of ten groups of notched concrete beams with 3D, 4D and 5D steel fibers. Results showed that the σ-w relationship of SFRC are changed from strain softening to strain hardening with increasing fiber volume fraction and number of fiber end hooks. The concrete beams with 4D and 5D steel fibers possess the higher flexural properties than the concrete beams with 3D steel fibers. In addition, the proposed analytical solutions and inverse analysis method could be applied to notched and unnotched SFRC beams with 3D, 4D and 5D steel fiber.